Effect of Platelet Lysate on Human Cells Involved in Different Phases of Wound Healing - Chiara Barsotti, Maria (Public Library of Science, 2013)
BACKGROUND: Platelets are rich in mediators able to positively affect cell activity in wound healing. Aim of this study was to characterize the effect of different concentrations of human pooled allogeneic platelet lysate on human cells involved in the different phases of wound healing (inflammatory phase, angiogenesis, extracellular matrix secretion and epithelialization). METHODOLOGY/PRINCIPAL FINDINGS: Platelet lysate effect was studied on endothelial cells, monocytes, fibroblasts and keratinocytes, in terms of viability and proliferation, migration, angiogenesis, tissue repair pathway activation (ERK1/2) and inflammatory response evaluation (NFκB). Results were compared both with basal medium and with a positive control containing serum and growth factors. Platelet lysate induced viability and proliferation at the highest concentrations tested (10% and 20% v/v). Whereas both platelet lysate concentrations increased cell migration, only 20% platelet lysate was able to significantly promote angiogenic activity (p<0.05 vs. control), comparably to the positive control. Both platelet lysate concentrations activated important inflammatory pathways such as ERK1/2 and NFκB with the same early kinetics, whereas the effect was different for later time-points. CONCLUSION/SIGNIFICANCE: These data suggest the possibility of using allogeneic platelet lysate as both an alternative to growth factors commonly used for cell culture and as a tool for clinical regenerative application for wound healing.